(3cJGH ehGYX GdCHQGQs - (3HjHQS GdOhGOGQs ((3OjfGQ GdeMeOi GdfHhi s)
(3ChdgG (B:s
(3bGd GdeUfa hbO LeYJ ai cJGHi gPG ef GdBjGJ hGdMce hGdPcQ hGdehGYX hLYdJg NeSjf HGHkG hSejJg ehGYX GdCHQGQ s
(3BNQgG (B:s
(3hGdahR HGdLfI hGdfLGI ef GdfGQ hLYdfG ef GdBefjf jhe GdOjf jhe dGjfaY eGd hdGHfhf hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs